Risk perception and usage of non-occupational post-exposure prophylaxis among fisherfolk in Ggulwe parish on the shores of Lake Victoria in central Uganda - Bahikire, Daraus; Nanyingi, Miisa; Atuhairwe, Christine; Matama, Catherine; Ninsiima, Lesley Rose; Bbuye, Mudarshiru (Frontiers in Public Health, 2023)
The use of non-occupational post exposure prophylaxis (nPEP) to prevent HIV acquisition among those exposed as an approach to HIV prevention has expanded in Uganda. Although there are increased efforts to avail nPEP services among at most risk populations, usage of nPEP medicines remains low. Therefore, this study examined the risk perception and usage of non-occupational post exposure prophylaxis (nPEP) among fishing folk of Ggulwe fishing parish, Bussi Sub County, Wakiso district. Methods A cross sectional study among adults was carried out from October 2020 to January 2021 in Ggulwe Parish, Bussi sub county, Wakiso district to examine the usage of nPEP and factors influencing the usage. Data were collected using semi-structured questionnaires, and key informants’ interviews conducted among health care providers and the local leadership. The quantitative data were summarized at bivariate and multivariate using logistic regression and qualitative data were analyzed thematically to enrich the quantitative results. Results Overall, 248 fishing folk encountered an event that required the use of nPEP and of these 55/248 (22.2%) of all were able to use nPEP to prevent them from acquiring HIV. Usage of nPEP among adults in Bussi Sub-county Wakiso district was associated with; not knowing that HIV can be prevented using nPEP medicines (AOR:0.1, 95%CI 0.03-0.36, p<0.001) (), lack of knowledge of the existence of nPEP (AOR: 0.3, 95%CI 0.13 -0.76, p=0.01 (), the perception that nPEP can effectively prevent HIV infection after exposure (AOR 0.0586, 95% CI: 0.0177-0.1944, p<0.001), and the community’s opinion affecting the willingness to take nPEP (AOR 0.1924, 95%CI: 0.0380-0.9727, p=0.0462). Conclusion Usage of nPEP among fishing-folk was low (22.2%). The low usage of nPEP was associated with lack of knowledge and awareness about nPEP.This effort to improve the usage nPEP should include community sensitization and the HIV infection prevention using nPEP as where awareness about HIV infection exposures and the risk of HIV infection during the during non-occupational exposures.